The Influence of Health Service Management and Leadership on Employee Performance: The Moderating Role of Digitalization at Public Health Centers in Serang regency - Siti Saroh; Gema Ika Sari; Udin Suadma (STIE Amkop Makassar, 2026)
The research is motivated by suboptimal employee performance, persistent service inefficiencies, and uneven implementation of digitalization. Therefore, a model capable of explaining the relationship between variables is needed to improve the quality of health services. This study aims to analyze the influence of health service management and leadership on employee performance, with digitalization as a mediating variable, at public health centers in Serang Regency. The study employed a quantitative approach with explanatory research methods. The study population comprised civil servants at 15 inpatient public health centers (Puskesmas) in Serang Regency. The sample size was determined using proportionate random sampling, with 170 respondents. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through outer model and inner model testing, as well as direct and indirect hypothesis testing. The results of the study indicate that all constructs have met the validity and reliability criteria. The coefficient of determination shows that digitalization can be explained by service management and leadership by 80.4%, while employee performance is explained by 76.3%. Hypothesis testing proves that service management has a positive and significant effect on employee performance and digitalization, leadership has a positive and significant effect on employee performance and digitalization, and digitalization has a positive and significant effect on employee performance. In addition, digitalization is proven to significantly mediate the influence of service management and leadership on employee performance. This study concludes that improving the performance of Community Health Center employees is not only determined by the quality-of-service management and leadership, but also by the effective implementation of digitalization. These findings offer practical implications for Community Health Center managers to strengthen digital transformation, improve the quality-of-service management, and develop adaptive leadership to achieve more effective, efficient, and community-oriented health services.